Estratégia de produção no setor de serviços: um estudo de caso na Empresa Brasileira de Correios e Telégrafos - Cruz, Daniella Cipola (Universidade Federal de São Carlos, 2007)
The service industry is continuously growing, reaching positions of higher prominence in the world and Brazilian economies. Its position is relevant in the composition of worldwide GDP. Over the last few years, the contribution of the service sector in the Brazilian Gross Domestic Product has been holding around 60%. The case study on Empresa Brasileira de Correios e Telégrafos (ECT) was addressed to examine the impact of automation of parcels processing on the competitive objectives in a regional business unit and, thus, observe how automation contributed to improve achievement of the whole entity competitive objectives. The technological modernization and the introduction of mechanization in the operational processes provided relevant impacts on different areas to maintain competitiveness. The combination of technological modernization with mechanization of operational process required investments of significant value, however, with fundamental importance in accelerate parcels processing, rationalization of distribution logistics and the final delivery of parcels. Considering such implications, it is plausible to say that strong impact occurred on various decision areas, structural and infra-structural, involving decisions on capacity, facilities and technology which brought relevant changes in the planning and control and human resources systems. The evaluation of visits, interviews, operational performance indicators and costumer requirement/organization performance profiles, determined by the application of the Platts-Gregory methodology for strategy formulation, allowed to verify that the parcel processing automation in business units strategically located in regions of high volume of parcels showed improvement on operational area and provided viability to maintain and, in some costumer segments, to achieve higher market competitiveness.
Keywords: Estratégia de produção; Operações de serviço; Objetivos competitivos; Automação; Operations strategy; Service operation, Competitive objectives; Automation; ENGENHARIAS::ENGENHARIA DE PRODUCAO